Financial Innovation in Indian Banking: A Sectoral Analysis of Its Impact on Performance Metrics - Renuka Abburu, Dr. T. Kama Raju; Dr. G. Sudhakar (Journal of Informatics Education and Research, 2025)
The Indian banking sector has witnessed a transformative shift in recent decades due to rapid financial innovation driven by technological advancements, regulatory changes, and evolving customer expectations. This study aims to analyze the impact of financial innovation on the performance metrics of commercial banks in India, with a sectoral focus on public and private sector banks. Financial innovations such as mobile banking, digital wallets, internet banking, automated loan processing, and fintech partnerships have redefined operational efficiency, customer service, and competitive advantage. Using a comparative analytical framework, the study examines key performance indicators such as Return on Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Cost-to-Income Ratio over a defined period. Secondary data from a representative sample of public and private sector banks are analyzed to assess whether financial innovation has translated into measurable performance improvements and whether its impact varies across bank categories. The findings suggest that private sector banks have been more proactive in adopting innovative financial solutions, often leading to superior performance outcomes compared to their public counterparts. However, the study also highlights that the effectiveness of financial innovation is contingent on complementary factors such as organizational agility, customer adoption, regulatory support, and infrastructure readiness. This research study contributes to the broader understanding of innovation-driven growth in banking and offers practical implications for policymakers, bank management, and financial technology providers aiming to enhance the resilience and competitiveness of India’s banking ecosystem.